LOCAL WISDOM VALUES GOVERNANCE AS NON-FINANCIAL INTANGIBLE ASSETS IN SUPPORTING INDIGENOUS PEOPLES' SUSTAINABILITY IN KAMPUNG PULO KABUPATEN GARUT - Suarsa, Abin; Verawaty, Verawaty; Sugihyanto, Toto (2019)
The study entitled